A rare entity: Cystic lymphangioma of the duodenal bulb and successful treatment with polypectomy in an adult patient - Şimşek, Zahide; Yılmaz, Barış; Aktaş, Bora; Arıkök, Ata Türker; Çoban, Şahin (Turkish Journal of Gastroenterology, 2014)
Abstract Gastrointestinal tract lymphangiomas are extremely rarely seen. Here, we present the first case of lymphangioma of the duodenal bulb diagnosed with a deep bite on a bite endoscopic biopsy and treated with polypectomy.